Pendampingan Perhitungan Harga Pokok Produksi, Penentuan Harga Jual, serta Penyusunan Laporan Keuangan bagi Kelompok Wanita Tani - Putri, Aprilia Milanda; Arini, Arini; Kurniawan, Nauri; Pawistri, Altia; Nugraha, Danuarta; Firmansyah, Aditya; Ningsih, Cindy Rahayu; Firmansyah, Tegar Dwi; Ferro Nika Ningsih N, Putri Dwi (MENARA RIAU, 2025)
A Farmer Group is a group of farmers/livestock breeders/planters formed on the basis of shared interests, shared environmental conditions (social, economic, resources) and familiarity to improve and develop members' businesses. The purpose of this community service activity is to provide an understanding of the importance of planning, financial management, bookkeeping, calculating COGS, and net profit in a farmer group business. The community service activity is carried out in the form of training. The method used is the Chair of the Association contacts Agricultural Extension Workers and Gapoktani Supervisors. Then, the Agricultural Extension Workers and Supervisors contact and send invitations to farmer group members to attend training provided by the Accounting Department Association Team, FEB, Lancang Kuning University. The technical implementation of community service activities is by providing extension materials followed by discussions and questions and answers as well as simulations of cases faced by members of the women farmer group. The results of the community service implementation show that members of the Women Farmer Group gain an understanding of the importance of calculating COGS and business profits for the sustainability of their businesses.